Respon Pisang Sulindang (Musa Paradisiaca L.) terhadap Formulasi Media MS dengan Sitokinin - Wismantia, Welly; Rodinah, Rodinah; Hardarani, Novia (Universitas Lambung Mangkurat, 2023)
The availability of banana seeds, especially Sulindang bananas as a fruit commodity in South Kalimantan, cannot be met on a large scale. The problem is that Sulindang banana seeds are still produced conventionally that produce small amounts of weeds. The solution that can be done to get maximum seed yield is by tissue culture. The research aims to determine the influence of interaction between BAP and kinetin on the growth of banana weevil explant Sulindang. This study used RAL two factors in the form of kinetin concentration and BAP concentration, consisting of 4 levels of kinetin; k0 = 0 mg l-1 kinetin; k1 = 1 mg l-1 kinetin; k2 = 2 mg l-1 kinetin; k3 = 3 mg l-1 kinetin and consists of 4 levels of BAP; b0 = 0 mg l-1 BAP; b1 = 2 mg l-1 BAP; b2 = 2.5 mg l-1 BAP; b3 = 3 mg l-1 BAP. The observed variables are changes in the morphology of the explant, the time the buds appear, the number of buds, the number of leaves, the percentage of living explants, the percentage of explants of contamination and the percentage of browning. The results of this study showed that there was no interaction between various concentrations of BAP and kinetin with banana explant Sulindang in the in vitro growth response in MS media. The BAP concentration did not affect the growth of the Sulindang Alas banana weevil explants. Single factor kinetin 2 mg l-1 was able to give the best results on the percentage of live explants at week 3 and week 6, respectively 96.88% and 93.75%. Also gives the smallest percentage of contamination at week 3 of 3.13% and week 4 to week 6, respectively - 6.25%.